Higher Education Expansion and Labor Market Outcomes for Young College Graduates - Dongshu Ou; Zhong Zhao (Institute for the Study of Labor (IZA), 2016)
We examine the causal impact of China's higher education expansion on labor market outcomes for young college graduates using China's 2005 1% Population Sample Survey. Exploiting variation in the expansion of university spots across provinces and high school cohorts and applying a difference-in-differences model, we find that the expansion of higher education in China decreases unemployment rates, especially among males and high school graduates. However, the policy also decreases women's labor force participation and individual earnings in highly-skilled white-collar jobs. We further discuss potential channels affecting the observed outcomes. Our results illustrate the strong demand for a skilled labor force in China and the broad economic benefits of higher education.
Keywords: I23; I28; J31; O15; 330; higher education expansion; labor force participation; unemployment; wage; difference-in-differences